Politik Islam Klasik (Suksesi Kepemimpinan Muhammad SAW dan Khulafa’ Ar-Rasyidin) - Miftahur Ridho (Institut Ilmu Keislaman Zainul Hasan Genggong, 2015)
Islam as a religion that has the legal basis of the Qur'an and hadith is also a religion that is inseparable from the interaction of the country which is the social life. Prophet as uswatun hasanah in reality is a leader who is really capable of being a religious leader and head of state. However, after the the period of Prophet Muhammad, there is a disagreement about the next leader. This problem is more tapered after the leadership of Umar bin Khattab, and the peak is tahkim events or better known as arbitration. Then, this became the first political upheaval in the leadership of Islam. In the succession of leadership succession has experienced periods of tremendous political upheaval. Regardless of the condition of Islam is still able to accommodate plural society that in fact that Islam having a heyday in the first years. That is because Islam has a strong foundation in the excavation of any law. And of course the situation is an important lesson for Islam to always be careful about politics and power.